PEMBUATAN POMPA HYDRAM SEDERHANA DI DUSUN LEMPENGE DESA SINTUNG KECAMATAN PRINGGARATA KABUPATEN LOTENG - rudy sutanto; made wirawan; arif mulyanto; ida bagus alit; agus dwi catur (JURNAL KARYA PENGABDIAN, 2018)
Hydram pump is a process of converting kinetic energy and water motion force into dynamic pressure so as to cause a high-strength water hammer in the pipeline. This pressure causes the pump valve and the introductory valve in the pump tube to open and close in turn. Dynamic pressure is continued to produce compressive force in the feeding tube thus forcing the water to rise to the discharge pipe and pushed into the conductor pipe, thus the working principle of this pump is to double the strength of the water thrust. PPM was followed by 10 people consisting of community leaders, village officials and residents of Lempenge village, Sintung village, Pringgarata district, Central Lombok regency, interested in environmentally friendly technology, hydram pump technology. The following counseling of hydram pump introduction was conducted in Sintung village hall, Pringgarata district, Central Lombok district. The material provided includes the working principle of hydram pump, hydram pump components and design, how to measure flow or source discharge.Keywords: hydram pump, water hammer, thrust, flow rate